1987
DOI: 10.1111/j.1365-2648.1987.tb01323.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory teaching of patients: how effective is it?

Abstract: In order to evaluate the effectiveness of a structured respiratory teaching programme, clients with chronic obstructive pulmonary disease who were hospitalized in a 13-month period both prior to and following the implementation of the programme were compared on several parameters to assess changes in their ability to manage their disabilities. The study demonstrated that clients who participated in the teaching sessions had fewer hospital admissions, shorter lengths of hospital stay, and longer stays in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The predialysis patients had all participated in a patient education programme prior to starting dialysis treatment. Previous investigators have shown that educational interventions have enabled patients with chronic illness to adjust more readily to their situation and to accept treatment more readily (26)(27)(28). Participation in the patient education programme may help explain why patients' perception of overall health and anxiety in the present study did not change despite deterioration of renal function and initiation of maintenance dialysis.…”
Section: Discussionmentioning
confidence: 62%
“…The predialysis patients had all participated in a patient education programme prior to starting dialysis treatment. Previous investigators have shown that educational interventions have enabled patients with chronic illness to adjust more readily to their situation and to accept treatment more readily (26)(27)(28). Participation in the patient education programme may help explain why patients' perception of overall health and anxiety in the present study did not change despite deterioration of renal function and initiation of maintenance dialysis.…”
Section: Discussionmentioning
confidence: 62%
“…This was followed by a homebased individual training programme, and the level of satisfaction with health was sustained one year later (12). A nurse-led education programme resulted in patients requiring fewer hospital stays and of shorter duration after one year (13).…”
Section: Non-randomised Studies Performed In Hospitalmentioning
confidence: 99%
“…The patients' medical records were examined for background data, such as age, sex, occupation, civil status, type of housing, number of years since the disease was first diagnosed, FEV1, previous participation in out-patient COPD classes, and BMI. A questionnaire was constructed for use in a preand a post-test, based on previous studies on the subject of knowledge (11,13,15,16,19,20), selfcare (11, 13-16, 19, 20), motivation (19) and experiences of how COPD influences everyday life (11,12,15,(17)(18)(19)(20)(27)(28)(29). A team of healthcare professionals (physician, nurse, physiotherapist and assistant nurse) and a statistician assessed the validity of the questions, after which four patients with COPD tested the questionnaire following groupbased education.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both their knowledge of the disease and skill in managing it increased. Howard, Davies, and Roghmann (1987) reported that hospitalized patients who participated in a structured pulmonary teaching program required fewer admissions and stayed out of the hospital longer than those who did not participate. The elements most important in determining the length of hospital stay and the length of time patients were able to stay out of the hospital were the use of medications, control of the environment, and knowledge of the changes in the pulmonary system that occur with COPD.…”
mentioning
confidence: 99%